2011
DOI: 10.2298/tsci1102437a
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of natural convection in a prismatic enclosure

Abstract: Natural convection heat transfer and fluid flow have been examined numerically using the control-volume finite-element method in an isosceles prismatic cavity, submitted to a uniform heat flux from below. Inclined sides are maintained isothermal and vertical walls are assumed to be perfect thermal insulators, without symmetry assumptions for the flow structure. The aim of the study is to examine a pitchfork bifurcation occurrence. Governing parameters on heat transfer and flow fields are the Rayleigh number an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…In the study of Yejjer et al [16] concerning three-dimensional natural convection and entropy generation in an inclined solar collector equipped with partitions, results are reported in terms of isosurfaces of temperature, isotherms, particles trajectories, velocity vector projection, average Nusselt number along the absorber plate and entropies generation contours. Aich et al [17] made a numerical analysis of natural convection in parismatic enclosure that looks like a monochapel greenhouse; he found that heat transfer increases with increasing Rayleigh number and decreases with increasing aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Yejjer et al [16] concerning three-dimensional natural convection and entropy generation in an inclined solar collector equipped with partitions, results are reported in terms of isosurfaces of temperature, isotherms, particles trajectories, velocity vector projection, average Nusselt number along the absorber plate and entropies generation contours. Aich et al [17] made a numerical analysis of natural convection in parismatic enclosure that looks like a monochapel greenhouse; he found that heat transfer increases with increasing Rayleigh number and decreases with increasing aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Lo and Novoselac [15] pointed out that the position of the outlet opening at the leeward façade only has a small impact on the volume flow rate, however, they analyzed a position of the outlet opening that is at the same level as the inlet opening, which is not the case in the current study. Aich et al [16] carried out a 2-D numerical study of natural convection flows in a prismatic cavity. It has been found that a considerable proportion of the heat transfer across the inclined walls of the enclosure takes place near the intersection of the adiabatic vertical walls and cold inclined walls.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of convective energy transfer regimes play an important role in science and engineering. Solutions of various natural convection problems in closed and semi-open cavities in non-conjugate [8][9][10][11][12][13][14] and conjugate [15][16][17][18] formulation are published. However, a special interest for practical applications represents investigation of jointly proceeding processes of conduction, convection, and radiation.…”
Section: Introductionmentioning
confidence: 99%